Aromatase inhibitors in premenopause: Great expectations fulfilled?. (November 2016) - Torrisi, Rosalba; Rota, Selene; Losurdo, Agnese; Zuradelli, Monica; Masci, Giovanna; Santoro, Armando
Highlights: Aromatase inhibitors plus GnRH a are active in HR +ve premenopausal breast cancer. Adjuvant exemestane clearly outperforms tamoxifen in high-risk and young women. Degree of ovarian suppression may be crucial for aromatase inhibitors activity. Monitoring estradiol upon AI therapy may be useful in young chemotherapy-naïve women. Abstract: Tamoxifen and GnRH analogues (GnRHa) represent the mainstay of endocrine manipulations in premenopausal women. The estrogen blockade obtained by aromatase inhibitors (AIs) plus GnRHa suppresses circulating estrogens more deeply than tamoxifen plus GnRHa. Retrospective and prospective evidence confirm a substantial activity for AIs and GnRHa in locally advanced and metastatic breast cancer. In early breast cancer inconsistent evidence emerged from 2 large randomized studies with anastrozole performing as tamoxifen in terms of DFS, but significantly worse as of OS while exemestane outperformed tamoxifen as of DFS particularly in very young and high-risk women. These findings support the use of AIs plus GnRHa in advanced breast cancer while long term efficacy and safety data are expected to define the appropriate indication of AIs in early breast cancer. In addition the clinical significance of persistent circulating estrogens and long term effects of estrogen deprivation in young women need further clarification.